2016
DOI: 10.1186/s13052-016-0255-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and sports activities in children and adolescents with solitary functioning kidney

Abstract: BackgroundAn increasing number of children with chronic disease require a complete medical examination to be able to practice physical activity. Particularly children with solitary functioning kidney (SFK) need an accurate functional evaluation to perform sports activities safely. The aim of our study was to evaluate the influence of regular physical activity on the cardiorespiratory function of children with solitary functioning kidney.MethodTwenty-nine patients with congenital SFK, mean age 13.9 ± 5.0 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…As individuals with a SFK have an increased risk of renal injury, sport participation should be stimulated rather than limited. Indeed, a recent study showed increased cardiorespiratory fitness after exercise training in children with a congenital SFK [ 59 ], as expected. In general, sport participation has been shown to reduce glomerular hyperfiltration [ 60 ], a finding which hopefully removes any remaining barrier in supporting a healthy and active lifestyle in individuals with a SFK even before they reach a state of chronic kidney disease (CKD), at which time exercise is again advised [ 61 ].…”
Section: Childhoodsupporting
confidence: 67%
“…As individuals with a SFK have an increased risk of renal injury, sport participation should be stimulated rather than limited. Indeed, a recent study showed increased cardiorespiratory fitness after exercise training in children with a congenital SFK [ 59 ], as expected. In general, sport participation has been shown to reduce glomerular hyperfiltration [ 60 ], a finding which hopefully removes any remaining barrier in supporting a healthy and active lifestyle in individuals with a SFK even before they reach a state of chronic kidney disease (CKD), at which time exercise is again advised [ 61 ].…”
Section: Childhoodsupporting
confidence: 67%
“…Therefore adequate renal protective treatment and blood pressure control in these patients should be promptly instituted [ 28 ]. Moreover, the increase in blood pressure should be also treated with an increase of sport activity; since it tends to improve the cardiorespiratory fitness in children with SFK [ 29 ] and kidney transplantation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In children with a congenital single kidney, physical activity improved aerobic capacity and exercise tolerance without increasing the risks of cardiovascular accidents [64], however, in the patients contact sports might be discouraged due to the increased risk of sport-related injury.…”
Section: Cardiorespiratory Fitness In Children With Chronic Kidney Di...mentioning
confidence: 99%